The Risk of Recurrence in Breast Cancer Patients Treated with Tamoxifen: Polymorphisms of CYP2D6 and ABCB1 - Teh, L. K.; Mohammed, N.I; Salleh, M.Z.; Rohaizak, M.; Shahrun, N.S; Saladina, J.J.; Shia, J.K.S.; Roslan, H.; Rajoo, T.S.; Muniandy, S.P.; Henry, G.; Abdullah Ngow, Harris; et al. (Springer, 2011)
CYP2D6 plays a major role in the metabolism of tamoxifen, and polymorphism of Pglycoprotein has been associated with resistance of many drug therapies. This study investigates the clinical impact of genetic variants of CYP2D6 and ABCB1 in breast cancer patients treated with tamoxifen. Blood samples from 95 breast cancer patients treated with tamoxifen were collected and genotyped for CYP2D6 and ABCB1 variants using allele-specific PCR method. Recurrence risks were calculated using Kaplan–Meier analysis and compared using the log-rank test. Patients carrying CYP2D6*10/*10 and heterozygous null allele (IM) showed higher risks of developing recurrence and metastasis (OR 13.14; 95% CI 1.57–109.94; P=0.004) than patients with CYP2D6*1/*1 and *1/*10 genotypes. Patients with homozygous CC genotypes of ABCB1 C3435T showed a shorter time to recurrence. Patients who were CYP2D6 IM and homozygous CC genotype of C3435T have statistically significant higher risks of recurrence (P=0.002). Similarly, median time to recurrence in these patients was only 12 months (95% CI=0.79–23.2) compared to those without this combination which was 48 months (95% CI=14.7–81.2). Patients with CYP2D6 IM and homozygous CC genotype of ABCB1 C3435T have shorter times to recurrence. The results confirmed the findings of previous studies and support FDA recommendation to perform pre-genotyping in patients before the choice of therapy is determined in breast cancer patients.